PENDAFTARAN KEMBALI HAK MEREK BARANG INDIKASI GEOGRAFIS - Haris Wiranata, I Ketut; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum, 2014)
In Article 23 the Government Regulation Number 51 in 2007 about Geographical Indications governed about the expiry of the protection of Geographical Indications which the typical characteristics and/or quality which became the basis for the protection of The Geographical Indication itself has none. About it, means that an item has received the certificate of Geographical Indications has undergone a change over the quality or characteristics of the goods quality itself, where such changes are in the form of improved quality and there is a loss of quality. This is a problem because it does not clearly regulated in The Government Regulation Number 51 in 2007 about this Geographical Indication, about how does the signup process again Branding Rights to a Geographical Indication of goods previously registered but are having a change of quality or quality of the goods and the characteristics stated its legal protection ends. With regard to this author interested in writing a paper entitled " Admission Back Branding Rights To Geographical Indications Of Goods". By using the juridical normative writing method, this paper will provide knowledge about the process of registration of a Geographical Indication of goods re previously registered but are having a change of quality or quality of the goods and the characteristics stated its legal protection ends. The back registration process Branding Rights to Geographical Indications of goods which are typical characteristics and getting back the original quality begins with the filing of a petition for registration of the Geographical Indication is continued with the Examination stage.In the stage of this examination, this Application will be reviewed administratively and substantively examined. After going through the stages of Examination, it will be followed by the Announcement made by the Directorate General of Intellectual Property. With the approval of the registration of The Brand Rights of return of goods of Geographical Indications, then such items back get the legal protection of Geographical Indications with a certificate as proof.
Keywords: Geographical Indications, The Back Registration Process